Statistics for business and economics David R. Anderson, Dennis J. Sweeney, Thomas A. Williams.. - Anderson, David R, 1941- (South Western-Thomson Learning, 2002)
This volume provides solid methodological development in the area of statistics for business & economics. The development of each technique is presented in an application setting with statistical results providing insights & solutions to problems.